A Nonspecific Penile Ulcer Leading to the Diagnosis of Wegener’s Granulomatosis - Ahmadnia, Hassan; Hasanzadeh Haddad, Amin; Darabi Mahboub, Mohammad Reza; Akhavan, Ali; Akhavan Rezayat, Ali Reza (Urology Journal, 2020)
The presented case describes a 53-year-old male who had been treated for non-specific cutaneous lesions for two months without any improvement. He was referred to our department after developing an erosive penile ulcer. Investigation for sexually transmitted diseases and Mycobacterium tuberculosis ended with negative results. Penile ulcer biopsy suggested the diagnosis of Wegener’s granulomatosis (WG). The patient presented with upper respiratory tract symptoms during this period. Measuring antineutrophil cytoplasmic antibodies (c-ANCA), confirmed the diagnosis. Immunosuppressive therapy was initiated and resulted in a favorable response.